Transnational Islam and Muslim Politics: Policies, Identities, and Ideologies - Koroglu, Ahmet; Brodard, Baptiste (Istanbul University Press, 2024)
This book titled Transnational Islam and Muslim Politics: Policies, Identities, and Ideologies combines the important contributions of various researchers who've presented their in tellectual endeavor on transnational Islam. As a result, this book represents a bold transversal reflection on recent evolutions in transnational Islam by delving into its various dimensions in the realms of politics, identity, and ideology. This book seeks to explore the complexities and dynamics of transnational Islam as a phenomenon that transcends national borders by linking Muslims from diverse cultural and ethnic backgrounds as well as from different ideo logical and theological influences. Aside from the chapters expounding on various expres sions of Sunnism, the volume also integrates a contribution on Shiite Islam. The authors of the volume are distinguished researchers from different corners of the world, each bringing their unique expertise and perspectives to the table. A brief glance at the book's various chap ters reveals this wide diversity of geographical and cultural focus.